Empatia e comportamentos antissociais na adolescência: um estudo correlacional - Claro, Leila Maria Piasentin (2023)
This dissertation was produced next to Post Graduation Program on Psychology at Federal University of Santa Maria, on the research line in Health Psychology, Human Sciences, Psychological Evaluation and Social Cognition, whose state delimited the following program: on what extent is scale PCL: YV sensitive to antisocial characterists in community sample in which the participants don’t presental mental disorders associated to psychopathy? Using psychological evaluation the research aimed to investigate the correlation between scales EMRI, EASME-A e PCL:YV in a community sample of adolescentes of public schools of a municipality inside Rio Grande do Sul. The sample checked low score in the inventory PCL: YV for characteristics of traces of psychopathy not stating diagnosis of psychopathy in the adult phase as well as high score for empaty levels. The findings identified negative correlation between the EMRI and PCL:YV in the factors “Empathic Consideration”, “Perspective Taking” and on “Global Empathy” levels. The results of the study revealed that as smaller the traces of empathy in adolescents, the higher the empathy levels. Therefore, adolescents with high levels of emphaty present greater well being, as well as preserve their interpersonal relationships, familiar and affections, making then more stable, pleasant and lasting.